Tunable and Switchable Multi-Wavelength Erbium-Doped Fiber Laser Based on Composite Structure Filter - Boya Shi; Chang Liu; Xinyan Lei; Junfa Zhao; Shuxia Yan (Photonics, 2022)
A multi-wavelength erbium-doped fiber laser (MW-EDFL) with wide tuning range, switching and adjustable wavelength interval is designed and tested, which is based on a composite filter. The filter consists of a tapered microfiber coupler loop (TMCL) with a nested single mode fiber (SMF)-two mode fiber (TMF)-SMF (STS) structure, which has a comb spectrum with obvious envelope and uniform fluctuation. Our experimental and theoretical results show that the laser can output thirteen wavelengths, when the angles of two polarization controllers (PCs) in the TMCL are accurately set. Moreover, by adjusting the PCs, the tuning range of single- to sextuple-wavelength can reach about 40 nm. Six non-adjacent multi-wavelength outputs can be observed in some specific polarization states. The maximum side-mode suppression ratio (SMSR) of the output laser is 40.6 dB. Compared with other multi-wavelength EDFL, the output characteristics of the laser, such as the adjustability and flexibility of wavelength spacing and the switch-ability of wavelength number, have been improved.